2010
DOI: 10.1055/s-0030-1249795
|View full text |Cite
|
Sign up to set email alerts
|

Ergebnisse einer Befragung zur Vereinbarkeit von klinischer und akademischer Entwicklung an orthopädischen und unfallchirurgischen Universitätskliniken in Deutschland

Abstract: Individual solutions seem to be necessary to achieve a scheduled efficiency of clinical and research careers. This includes structural developments (like a professionally headed lab) and the establishment of dynamic clinical structures. It seems possible that the clinical organisation of physicians in teams might offer solutions to cope with the demands of surgical training and clinical care on the one hand and research on the other hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Earlier investigations in orthopedic and trauma departments [14] as well as in general surgery [15] also identified that the incompatibility of clinical and research obligations was the key obstacle to the conduct of research projects in Germany, especially during residency programs. A recent survey among residents in ophthalmology at German university hospitals [16] revealed that 80% were never offered relief from clinical work to pursue their scientific activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier investigations in orthopedic and trauma departments [14] as well as in general surgery [15] also identified that the incompatibility of clinical and research obligations was the key obstacle to the conduct of research projects in Germany, especially during residency programs. A recent survey among residents in ophthalmology at German university hospitals [16] revealed that 80% were never offered relief from clinical work to pursue their scientific activities.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of support from senior researchers was found to be an obstacle to carrying out scientific projects for residents in ophthalmology [16]. Bernstein et al [14] revealed that junior physicians at university hospitals ranked clinical and surgical experience as being more important to their career development than scientific achievements; the second highest priority was given to a satisfying private life.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results of decreasing research productivity in surgical research journals were not only described for general surgery in the United States (3), but also for German general surgery based on Langenbeck's Archive of Surgery (25) as well as for the United Kingdom and Ireland (26). Increasing methodological demands cannot be met by research activities following a regular work day, which is still common despite all pleas against it (25,(27)(28)(29) and does not exclude pediatric surgery (30). It therefore represents an inexpungable obstacle for nonacademic surgeons in Germany as non-clinical duties are neither financially compensated nor perceived part of the contract and thus scientific work takes place during spare time and offhours (27,28).…”
Section: A Similar Situation In General Surgerymentioning
confidence: 66%
“…Increasing methodological demands cannot be met by research activities following a regular work day, which is still common despite all pleas against it (25,(27)(28)(29) and does not exclude pediatric surgery (30). It therefore represents an inexpungable obstacle for nonacademic surgeons in Germany as non-clinical duties are neither financially compensated nor perceived part of the contract and thus scientific work takes place during spare time and offhours (27,28). In German general surgery, the vast majority of operations are conducted at non-academic departments that do not participate in research (31).…”
Section: A Similar Situation In General Surgerymentioning
confidence: 99%
“…In einer Befragung zur Vereinbarkeit von klinischer und akademischer Entwicklung an orthopädischen und unfallchirurgischen Universitätskliniken in Deutschland erhielten Bernstein et al [1] [3,7,11,12]. Granger et al [6] haben dies an dem Beispiel einer einzelnen Klinik zeigen können: Mit Einführung wissenschaftlicher Koordinatoren, eines wissenschaftlichen Kurrikulums, der Etablierung von Forschungsteams und einer zentralisierten Forschungsdatenbasis stieg die wissenschaftliche Produktivität signifikant an.…”
Section: Materials Und Methodikunclassified